Contact model for elastoplastic analysis of half-space indentation by a spherical impactor. (15th April 2015) - Big-Alabo, Akuro; Harrison, Philip; Cartmell, Matthew P.
Highlights: A new contact model for post-yield indentation of a half-space target was developed. The model accounts for plastic deformation effects and is evaluated from physical properties. The model agrees with experimental data and compares well with other models. The model can be used for impact/indentation analysis of metals. An approach for evaluating maximum conditions of half-space impact is presented. Abstract: This paper presents a new contact model for analysis of post-yield indentation of a half-space target by a spherical indenter. Unlike other existing models, the elastoplastic regime of the present model was modelled using two distinct force–indentation relationships based on experimentally and theoretically established indentation characteristics of the elastoplastic regime. The constants in the model were derived from continuity conditions and indention theory. Simulations of the present model show good prediction of experimental data. Also, an approach for determining the maximum contact force and indentation of an elastoplastic half-space from the impact conditions has been proposed.